Background and precancerous processes in the vulva and vagina: etiology, pathogenesis, diagnosis and treatment - A. G. Solopova; E. V. Tselovalnikova; V. S. Moskvichyova; T. A. Blbulyan; A. S. Shkoda; A. D. Makatsariya (IRBIS LLC, 2019)
Leukoplakia, kraurosis and pointed condylomas (papillomas) of the vulva represent the group of background benign vulvar diseases. Vulvar and vaginal intraepithelial neoplasms are classified as premalignant conditions. The etiology and pathogenesis of these diseases are not entirely clear due to their complexity. Despite the easy visual assessment of anatomic areas involved in the pathological process, these diseases are rarely diagnosed at an early stage, which might indicate insufficient vigilance of doctors and patients in relation to the early symptoms. Therefore, this field of oncogynecology needs further development ln terms of diagnosisprevention, screening and treatment.